2021
DOI: 10.3390/biomedicines9121943
|View full text |Cite
|
Sign up to set email alerts
|

Azadirachtin Attenuates Lipopolysaccharide-Induced ROS Production, DNA Damage, and Apoptosis by Regulating JNK/Akt and AMPK/mTOR-Dependent Pathways in Rin-5F Pancreatic Beta Cells

Abstract: Pancreatic inflammation and the resulting cellular responses have been implicated in pancreatitis, diabetes, and pancreatic cancer. Inflammatory responses due to the bacterial endotoxin, lipopolysaccharide (LPS), have been demonstrated to alter cellular metabolism, autophagy, apoptosis, and cell proliferation in different cell populations, and hence increases the risks for organ toxicity including cancer. The exact molecular mechanism is however not clear. In the present study, we investigated the role and mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…In our previous study on Rin-5F cells (John and Raza, 2021), we also showed that LPS treatment caused a marked increase in ROS production, which leads to DNA damage and apoptosis. Our present study has further confirmed the consequences of high ROS production by measuring LPO and oxidative stress-sensitive enzymes, SOD, and catalase.…”
Section: Effects Of Azd/lps On Oxidative Stress and Redox Homeostasis...mentioning
confidence: 71%
See 4 more Smart Citations
“…In our previous study on Rin-5F cells (John and Raza, 2021), we also showed that LPS treatment caused a marked increase in ROS production, which leads to DNA damage and apoptosis. Our present study has further confirmed the consequences of high ROS production by measuring LPO and oxidative stress-sensitive enzymes, SOD, and catalase.…”
Section: Effects Of Azd/lps On Oxidative Stress and Redox Homeostasis...mentioning
confidence: 71%
“…Our recent study on Rin-5F cells ( John and Raza, 2021 ) showed LPS-induced caspase-3/8-dependent apoptosis followed by increased DNA fragmentation in LPS treated cells and AZD caused attenuation of the apoptotic damages by enhancing the autophagic repair process. Our present study has further demonstrated that intrinsic caspase-9, which is the initiator caspase of the apoptotic pathway in the mitochondria, was also activated by LPS treatment and AZD protected the cells against LPS–induced apoptosis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations